Evaluation of Corporate Sustainability Disclosure Practices in Listed Companies of the Baltic States - Jokūbauskas, Paulius Česlovas; Šalienė, Asta (Buhalterinės apskaitos teorija ir praktika, 2025)
The relevance and novelty of this study lie in the growing importance of corporate sustainability disclosure as a mechanism for enhancing transparency, accountability, and stakeholder trust. Despite the increasing regulatory emphasis across the European Union, a critical research gap remains: the sustainability reporting practices of listed companies in smaller-market economies, such as the Baltic States, have been underexplored. This study addresses the scientific question of how well listed companies in the Baltic region are adapting to the evolving EU sustainability regulatory environment, particularly in terms of the scope of sustainability disclosures. The methodology includes a systematic literature review and a document analysis of disclosures for the period 2021–2024. Using sustainability disclosure and assessment models based on GRI topic standards and ESRS standards, the study examines the sustainability level disclosure through the ESG approach and by sectors. The study reveals that publicly listed companies in the Baltic States show limited and uneven sustainability disclosure, with economic and social indicators particularly underreported, and environmental data often strategically selected rather than substantively addressed. Sectoral analysis highlights broader engagement in construction, food, and manufacturing sectors, while financial, retail, and real estate sectors lag behind in transparency, especially on social and environmental issues. ESRS-based disclosures show a focus on climate change and business conduct, but significant gaps persist in areas such as pollution, biodiversity, and value chain impacts, indicating selective implementation and limited regulatory readiness.